Silicon-containing monomer and photocuring adhesive

By using silicon-containing monomers in the photocuring adhesive, the performance of the adhesive is improved by using its active groups, the problems of poor bubble generation and permeability are solved, and efficient and durable bonding effect is achieved.

CN119798299AActive Publication Date: 2025-04-11GUANGZHOU HUITIAN FINE CHEM
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411794800.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-11
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

Existing photocuring adhesives are prone to bubbles during the production process, which has poor permeability and affects the adhesive effect.

Method used

Silicon-containing monomers are used to improve the flexibility, adhesion and transparency of the adhesive through active groups such as siloxane bonds, urea bonds, carbamate bonds and acrylate double bonds, and enhance crosslinking density in humid environments.

Benefits of technology

The photocuring adhesive is achieved with few bubbles, strong adhesiveness, high transparency and good durability, which simplifies the raw material formula and reduces the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798299A_ABST
    Figure CN119798299A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-containing monomer and a photocuring adhesive, and belongs to the technical field of functional materials. According to the silicon-containing monomer provided by the invention, a siloxane bond can endow a system with good flexibility, adhesive force, water resistance, transparency and other properties, and in a humid environment, the siloxane bond can be hydrolyzed and crosslinked with water, so that the adhesive force can be enhanced while the crosslinking density is improved; the urea bond and the carbamate bond can improve the hydrogen bond concentration of the system, so that the adhesion is improved; acrylate double bonds are beneficial to rapid curing of the monomer, and the preparation efficiency is improved. The silicon-containing monomer provided by the invention can be used for preparing a photocuring adhesive with few bubbles, strong adhesive strength, high transparency and good durability, and firm adhesion among various materials is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, and in particular relates to a silicon-containing monomer and a photocurable adhesive. Background Art

[0002] Photocuring adhesives are a type of material that can cure rapidly under ultraviolet (UV) or visible light irradiation. They have the advantages of fast curing speed, low energy consumption, environmental friendliness, and low energy consumption. The principle mainly utilizes the irradiation of ultraviolet or visible light. The photoinitiator absorbs light of a specific wavelength and decomposes to produce active free radicals or cations. These active substances then initiate the polymerization reaction of monomers and prepolymers to form a cross-linked network structure, thereby causing the liquid to cure rapidly.

[0003] Traditional light-curing adhesives on the market are usually composed of various modified acrylic resins, and different additives are added according to different requirements to meet the bonding needs of different materials. Although the progress and development of light-curing adhesives have greatly improved the efficiency of bonding and sealing in chemical production and daily life, there are still some technical challenges. For example, it is difficult to avoid the generation of bubbles during the production process, and additional defoaming agents need to be added, which will affect the performance of the adhesive; for example, the poor permeability of the adhesive leads to insufficient cross-linking of the internal resin, which reduces the effect of the adhesive. Summary of the invention

[0004] In order to overcome at least one of the problems existing in the above-mentioned prior art, one of the objectives of the present invention is to provide a silicon-containing monomer, which has good flexibility, adhesion and water resistance and can be used to prepare a photocurable adhesive with good performance.

[0005] A second object of the present invention is to provide a method for preparing the above silicon-containing monomer.

[0006] A third object of the present invention is to provide a light-curing adhesive.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The first aspect of the present invention provides a silicon-containing monomer, wherein the structural formula of the silicon-containing monomer is shown in the following formula (I):

[0009]

[0010] In formula (I), R1 represents a C1-C30 alkyl group or a C6-C30 aromatic group; R2 represents a C1-C30 alkyl group, and is optionally interrupted by one or more O atoms, and / or interrupted by one or more -C(=O)O-; R3 represents a C1-C30 alkyl group; R4-R6 each independently represent a C1-C20 alkyl group.

[0011] Preferably, R1 represents a C3-C20 branched or straight chain alkyl group, a C3-C20 cycloalkyl group substituted or unsubstituted by a C1-C5 alkyl group, or a C6-C20 aromatic group substituted or unsubstituted by a C1-C5 alkyl group; further preferably, R1 represents

[0012]

[0013] It should be noted that the "*" in the present invention represents the connection site of the group in formula (I).

[0014] Preferably, R2 represents a C3-C20 alkyl group, and is optionally interrupted by 1-10 O atoms, and / or by 1-10 -C(=O)O- atoms; further preferably, R2 represents

[0015]

[0016] Preferably, R3 represents a C1-C20 alkyl group; more preferably, R3 represents a C3-C12 alkyl group.

[0017] Preferably, R4 to R6 each independently represent a C1 to C10 alkyl group; more preferably, R4 to R6 each independently represent a methyl group or an ethyl group.

[0018] In some specific embodiments of the present invention, the silicon-containing monomer contains a relatively long chain segment, which can increase the flexibility of the adhesive to a certain extent. In addition, since the silicon-containing monomer contains urea bonds, the hydrogen bond concentration can be increased, thereby enhancing the adhesion of the adhesive.

[0019] Preferably, the silicon-containing monomer comprises:

[0020]

[0021]

[0022] The second aspect of the present invention provides a method for preparing the silicon-containing monomer according to the first aspect of the present invention, comprising the following steps:

[0023] S1, mixing the diisocyanate containing R1 with a polymerization inhibitor, adding an acrylate containing R2 and a catalyst, and performing a first polymerization reaction to obtain an intermediate;

[0024] S2, mixing the intermediate obtained in step S1 with a silane coupling agent containing R3 to R6, and performing a second polymerization reaction to obtain the silicon-containing monomer.

[0025] Preferably, the diisocyanate containing R1 includes toluene diisocyanate Isophorone diisocyanate Methylene diphenyl diisocyanate Dicyclohexylmethane diisocyanate or hexamethylene diisocyanate At least one of .

[0026] The present invention uses diisocyanate as one of the reaction raw materials, one end of which needs to be grafted with an acrylic acid double bond so that it can participate in curing, and the other end introduces a siloxane bond to improve the performance of the adhesive.

[0027] Preferably, the acrylic acid ester containing R2 includes 2-(acryloyloxy)ethyl-6-hydroxyhexanoate 2-(Acryloyloxy)ethyl dicaprolactone or 20-hydroxy-3,6,9,12,15,18-hexaoxa-eicosyl-1-acrylate At least one of .

[0028] Preferably, the silane coupling agent containing R3 to R6 includes 3-aminopropyltriethoxysilane 3-Aminopropyltrimethoxysilane 4-Aminobutyltriethoxysilane Aminomethyltriethoxysilane or 11-aminoundecyltriethoxysilane At least one of .

[0029] Preferably, the polymerization inhibitor includes at least one of hydroquinone, imidazoline, catechol or hydroquinone; further preferably, the polymerization inhibitor includes at least one of hydroquinone, imidazoline or catechol.

[0030] Preferably, the catalyst comprises at least one of bis(dimethylaminoethyl)ether, pentamethyldiethylenetriamine, dimethylcyclohexylamine, dibutyltin dilaurate, organic bismuth or triazine trimerization catalysts; further preferably, the catalyst comprises dibutyltin dilaurate, organic bismuth or a combination thereof.

[0031] Preferably, the molar ratio of the diisocyanate containing R1 to the acrylate containing R2 is 1:(1-1.1); more preferably, it is 1:(1.02-1.05).

[0032] Preferably, the molar ratio of the intermediate to the silane coupling agent containing R3 to R6 is 1:(1 to 1.1); more preferably, it is 1:(1 to 1.05).

[0033] Preferably, the dosage of the polymerization inhibitor is 600-1000 ppm based on the total mass of the diisocyanate containing R1 and the acrylate containing R2.

[0034] Preferably, the amount of the catalyst used is 1000-2000 ppm based on the total mass of the diisocyanate containing R1 and the acrylate containing R2.

[0035] Preferably, the reaction temperature of the first polymerization reaction is 40-55°C; more preferably 42-50°C.

[0036] Preferably, the reaction time of the first polymerization reaction is 1 to 4 hours; more preferably, it is 1.5 to 3 hours.

[0037] Preferably, the reaction temperature of the second polymerization reaction is 50-80°C; more preferably 55-70°C.

[0038] Preferably, the reaction time of the second polymerization reaction is 1 to 4 hours; more preferably, it is 1.5 to 3 hours.

[0039] Preferably, step S1 and step S2 are performed under an atmosphere of protective gas; further preferably, the protective gas includes at least one of nitrogen, argon or helium; even more preferably, the protective gas includes nitrogen, argon or a combination thereof.

[0040] Preferably, the step S1 further comprises the step of measuring the NCO group content of the reaction product. When the measured NCO group content is 45-55% of the NCO group content of the diisocyanate containing R1, the first polymerization reaction is stopped to obtain an intermediate.

[0041] Preferably, the step S2 further comprises the step of measuring the NCO group content of the reaction product. When the measured NCO group content is lower than 0.1%, the second polymerization reaction is stopped to obtain the silicon-containing monomer. In some specific embodiments of the present invention, the method for measuring the NCO group content can be selected from infrared spectroscopy. When the infrared detection finds that 2260cm -1 When the characteristic peak belonging to the NCO group disappears, the second polymerization reaction is stopped to obtain the silicon-containing monomer.

[0042] The third aspect of the present invention provides a photocurable adhesive, comprising the following preparation materials: a base resin, a photoinitiator, and the silicon-containing monomer described in the first aspect of the present invention.

[0043] Preferably, the photocurable adhesive comprises the following raw materials in parts by weight: 30 to 60 parts of base resin, 3 to 8 parts of photoinitiator, and 20 to 50 parts of silicon-containing monomer.

[0044] Preferably, the matrix resin includes at least one of polyurethane acrylic resin, epoxy resin or epoxy acrylate; further preferably, the matrix resin is selected from polyurethane acrylic resin.

[0045] The silicon-containing monomer of the present invention can be compounded with a matrix resin such as polyurethane acrylate resin, epoxy resin, epoxy acrylate, etc. to obtain a light-curing adhesive with good bonding performance; wherein the polyurethane acrylate resin and the silicon-containing monomer of the present invention have a more similar structure and good compatibility, and the polyurethane acrylate resin can also provide a carbamate bond, further enhancing the hydrogen bond concentration of the system, thereby improving the bonding strength of the adhesive.

[0046] Preferably, the photoinitiator comprises at least one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide or benzophenone.

[0047] Preferably, the raw materials for preparing the photocurable adhesive further include acrylate monomers, defoamers or a combination thereof; further preferably, the raw materials for preparing the photocurable adhesive further include acrylate monomers, or acrylate monomers and defoamers.

[0048] Preferably, the raw materials for preparing the photocurable adhesive do not include a defoaming agent.

[0049] Preferably, the photocurable adhesive comprises the following raw materials in parts by mass: 30 to 60 parts of base resin, 3 to 8 parts of photoinitiator, 20 to 50 parts of silicon-containing monomer, 10 to 30 parts of acrylate monomer, and 0 to 2 parts of defoaming agent; further preferably, the photocurable adhesive comprises the following raw materials in parts by mass: 30 to 60 parts of base resin, 3 to 8 parts of photoinitiator, 20 to 50 parts of silicon-containing monomer, and 10 to 30 parts of acrylate monomer; and does not include a defoaming agent.

[0050] Preferably, the acrylate monomer includes at least one of acryloylmorpholine, methyl acrylate, ethyl acrylate, 2-methyl methacrylate or 2-ethyl methacrylate; further preferably, the acrylate monomer is selected from acryloylmorpholine.

[0051] In the present invention, the addition of acrylate monomers can adjust the viscosity of the adhesive and adjust the bonding performance.

[0052] The beneficial effects of the present invention are as follows: in the silicon-containing monomer of the present invention, the siloxane bond can give the system good flexibility, adhesion, water resistance, transparency and other properties, and in a humid environment, the siloxane bond can be hydrolyzed and cross-linked with water, which can increase the cross-linking density and enhance the adhesion; the urea bond and the urethane bond can increase the hydrogen bond concentration of the system, thereby improving the adhesion; the acrylate double bond is conducive to the rapid curing of the monomer and improves the preparation efficiency. By using the silicon-containing monomer of the present invention, a light-curing adhesive with few bubbles, strong adhesion, high transparency and good durability can be prepared, and a firm bonding between a variety of materials can be achieved.

[0053] Specifically, compared with the prior art, the present invention has the following advantages:

[0054] 1. In the preparation method of the silicon-containing monomer of the present invention, the acrylate double bond required for curing is first introduced by reacting hydrogen bonds with isocyanate groups, and then the amino groups are reacted with isocyanate groups to generate substituted ureas. The reaction is rapid and the steric hindrance caused by the previous step reaction can be ignored, making the preparation process of the monomer more convenient. In addition, the acrylate raw materials used in the present invention contain relatively long chain segments and active double bonds, which can not only give the adhesive flexibility but also participate in curing.

[0055] 2. The photocurable adhesive of the present invention has active groups such as siloxane bonds, urea bonds, carbamate bonds and acrylate double bonds due to the introduction of silicon-containing monomers. It can obtain good flexibility and adhesion while reducing the impact of environmental water vapor on the product, enhancing practicality and durability, and can reduce the viscosity of the system and the generation of internal bubbles, thereby increasing the transparency and durability of the adhesive and obtaining good adhesion; the silicon-containing monomer combined with the matrix resin (such as polyurethane acrylate resin, etc.) can further enhance the hydrogen bond concentration of the system, thereby improving the adhesion of the adhesive.

[0056] 3. The photocurable adhesive of the present invention can be cured and cross-linked under ultraviolet light, and is more convenient to use than traditional liquid adhesives; and the adhesive has lower surface energy and better defoaming performance, thereby ensuring that fewer bubbles are generated without adding a defoaming agent, thereby obtaining a product with good transparency and durability, which is also conducive to simplifying the raw material formula and reducing the preparation cost; in addition, the adhesive has good flexibility, heat resistance and durability, and can be widely used in bonding between various materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 Schematic diagram of the test process for testing the bonding performance of the photocurable adhesive of Adhesive Examples 1 to 5 and Adhesive Comparative Example 1.

[0058] Figure 2 These are water contact angle pictures of adhesive examples 1 to 5 and adhesive comparative example 1. DETAILED DESCRIPTION

[0059] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.

[0060] Silicon-containing monomer example 1

[0061] This example provides a silicon-containing monomer M1, and the specific preparation process is as follows:

[0062] S1. (44.44 g, 0.20 mol) of isophorone diisocyanate and (0.14 g, 1500 ppm) of catechol as an inhibitor were added to a 250 ml four-necked flask, a stirring device was installed and nitrogen was introduced, and (46.51 g, 0.202 mol) of 2-(acryloyloxy)ethyl-6-hydroxyhexanoate was slowly added using a feed device, and the feed time was controlled between 0.5 and 1 hour, during which the reaction temperature was controlled at 40°C to 50°C, and the system was stirred evenly until the system no longer released heat, and then (0.07 g, 800 ppm) of dibutyltin dilaurate was added after being kept warm for 0.5 h. After the reaction no longer released heat, the temperature was kept at 45°C ± 2°C for 2 hours, and the NCO value was titrated until the conversion rate reached 50%, and the reaction was stopped to obtain a semi-blocked acrylic polyurethane;

[0063] S2. Control the temperature of the above mixed solution at 45℃±2℃, pass nitrogen, slowly add (36.57g, 0.204mol) 3-aminopropyltrimethoxysilane dropwise, control the addition time between 0.5-1 hour, stir evenly until the system no longer releases heat, keep warm at 60℃±2℃ for 2 hours, titrate the NCO value until blank, and obtain the silicon-containing photocurable monomer M1.

[0064] The specific structural formula of the silicon-containing photocurable monomer M1 is:

[0065]

[0066] Deuterated chloroform is used as a solvent to dissolve the monomer M1 and then perform H-NMR analysis, with TMS used as an internal standard. 1H NMR (300 MHz): δ(t, 1H, -CH=CH2)=6.12 ppm; δ(s, 3H, -Si-O-CH3)=3.56 ppm; δ(s, 3H, -CH3 on the aliphatic ring)=0.88 ppm.

[0067] Silicon-containing monomer example 2

[0068] This example provides a silicon-containing monomer M2, and the specific preparation process is as follows:

[0069] S1. (34.83 g, 0.20 mol) toluene diisocyanate and (0.12 g, 1500 ppm) hydroquinone as an inhibitor were added to a 250 ml four-necked flask, a stirring device was installed and nitrogen was introduced, and (46.51 g, 0.202 mol) 2-(acryloyloxy)ethyl-6-hydroxyhexanoate was slowly added using a feed device, and the feed time was controlled between 0.5 and 1 hour, during which the reaction temperature was controlled at 40°C to 50°C, and the system was stirred evenly until the system no longer released heat, and then (0.06 g, 800 ppm) dibutyltin dilaurate was added after being kept warm for 0.5 h. After the reaction no longer released heat, the temperature was kept at 45°C ± 2°C for 2 hours, and the NCO value was titrated until the conversion rate reached 50%, and the reaction was stopped to obtain a semi-blocked acrylic polyurethane;

[0070] S2. Control the temperature of the above mixed solution at 45℃±2℃, pass nitrogen, slowly add (36.57g, 0.204mol) 3-aminopropyltrimethoxysilane dropwise, control the addition time between 0.5-1 hour, stir evenly until the system no longer releases heat, keep warm at 60℃±2℃ for 2 hours, titrate the NCO value until blank, and obtain the silicon-containing photocurable monomer M2.

[0071] The specific structural formula of the silicon-containing photocurable monomer M2 is:

[0072]

[0073] Deuterated chloroform is used as a solvent to dissolve the monomer M2 and then perform H-NMR analysis, with TMS used as an internal standard. 1 H NMR (300 MHz): δ(t, 1H, -CH=CH2)=6.14 ppm; δ(s, 3H, -Si-O-CH3)=3.54 ppm; δ(s, 3H, -CH3 on benzene ring)=2.18 ppm.

[0074] Silicon-containing monomer example 3

[0075] This example provides a silicon-containing monomer M3, and the specific preparation process is as follows:

[0076] S1. (44.44 g, 0.20 mol) of isophorone diisocyanate and (0.14 g, 1600 ppm) of hydroquinone as an inhibitor were added to a 250 ml four-necked flask, a stirring device was installed and nitrogen was introduced, and (46.51 g, 0.202 mol) of 2-(acryloyloxy)ethyl-6-hydroxyhexanoate was slowly added using a feed-addition device, and the feed time was controlled between 0..5 and 1 hours, during which the reaction temperature was controlled at 40°C to 50°C, and the system was stirred evenly until the system no longer released heat, and then (0.08 g, 900 ppm) of organic bismuth was added after being kept warm for 0.5 hours. After the reaction no longer released heat, the temperature was kept at 45°C ± 2°C for 2 hours of heat preservation, and the NCO value was titrated until the conversion rate reached 50%, and the reaction was stopped to obtain a semi-blocked acrylic polyurethane;

[0077] S2. Control the temperature of the above mixed solution at 45℃±2℃, pass nitrogen, slowly add (48.02g, 0.204mol) 4-aminobutyltriethoxysilane dropwise, control the addition time between 0.5-1 hour, stir evenly until the system no longer releases heat, keep warm at 60℃±2℃ for 2 hours, titrate the NCO value until blank, and obtain the silicon-containing photocurable monomer M3.

[0078] The specific structural formula of the silicon-containing photocurable monomer M3 is:

[0079]

[0080] Deuterated chloroform is used as a solvent to dissolve the monomer M3 and then perform H-NMR analysis, with TMS used as an internal standard. 1 H NMR (300 MHz): δ(t, 1H, -CH=CH2)=6.15 ppm; δ(dd, 2H, -Si-O-CH2-CH3)=3.84 ppm; δ(s, 3H, -CH3 on the aliphatic ring)=0.94 ppm.

[0081] Silicon-containing monomer example 4

[0082] This example provides a silicon-containing monomer M4, and the specific preparation process is as follows:

[0083] S1. (34.83 g, 0.20 mol) toluene diisocyanate and (0.16 g, 1500 ppm) imidazoline inhibitor were added to a 250 ml four-necked flask, a stirring device was installed and nitrogen was introduced, and (70.26 g, 0.204 mol) dicaprolactone-2-(acryloyloxy)ethyl ester was slowly added using a feed-addition device. The feed-addition time was controlled between 0.5 and 1 hour, and the reaction temperature was controlled at 40°C to 50°C during the period. After stirring evenly until the system no longer released heat, (0.10 g, 1000 ppm) organic bismuth was added after keeping warm for 0.5 h. After the reaction no longer released heat, the temperature was kept at 45°C ± 2°C for 2 hours of heat preservation reaction, and the NCO value was titrated until the conversion rate reached 50%, and the reaction was stopped to obtain a semi-blocked acrylic polyurethane;

[0084] S2. Control the temperature of the above mixed solution at 45℃±2℃, pass nitrogen, slowly add (48.02g, 0.204mol) 4-aminobutyltriethoxysilane dropwise, control the addition time between 0.5-1 hour, stir evenly until the system no longer releases heat, keep warm at 60℃±2℃ for 2 hours, titrate the NCO value until blank, and obtain the silicon-containing photocurable monomer M4.

[0085] The specific structural formula of the silicon-containing photocurable monomer M4 is:

[0086]

[0087] Deuterated chloroform is used as a solvent to dissolve the monomer M4 and then perform H-NMR analysis, with TMS used as an internal standard. 1 H NMR (300 MHz): δ(t, 1H, -CH=CH2)=6.13 ppm; δ(dd, 2H, -Si-O-CH2-CH3)=3.82 ppm; δ(s, 3H, -CH3 on benzene ring)=2.18 ppm.

[0088] Silicon-containing monomer example 5

[0089] This example provides a silicon-containing monomer M5, and the specific preparation process is as follows:

[0090] S1. (44.44 g, 0.20 mol) of isophorone diisocyanate and (0.18 g, 1600 ppm) of catechol inhibitor were added to a 250 ml four-necked flask, a stirring device was installed and nitrogen was introduced, and (70.26 g, 0.204 mol) of dicaprolactone-2-(acryloyloxy)ethyl ester was slowly added using a feed device, and the feed time was controlled between 0.5 and 1 hours, during which the reaction temperature was controlled at 40°C to 50°C, and the system was stirred evenly until the system no longer released heat, and then (0.10 g, 900 ppm) of dibutyltin dilaurate was added after being kept warm for 0.5 h. After the reaction no longer released heat, the temperature was kept at 45°C ± 2°C for 2 hours, and the NCO value was titrated until the conversion rate reached 50%, and the reaction was stopped to obtain a semi-blocked acrylic polyurethane;

[0091] S2. Control the temperature of the above mixed solution at 45℃±2℃, pass nitrogen, slowly add (39.44g, 0.204mol) aminomethyltriethoxysilane dropwise, control the addition time between 0.5-1 hour, stir evenly until the system no longer releases heat, keep warm at 60℃±2℃ for 2 hours, titrate the NCO value until blank, and obtain the silicon-containing photocurable monomer M5.

[0092] The specific structural formula of the silicon-containing photocurable monomer M5 is:

[0093]

[0094] Deuterated chloroform was used as a solvent to dissolve the monomer M5 and then perform H-NMR analysis, with TMS used as an internal standard. 1 H NMR (300 MHz): δ(t, 1H, -CH=CH2)=6.15 ppm; δ(dd, 2H, -Si-O-CH2-CH3)=3.85 ppm; δ(s, 3H, -CH3 on the aliphatic ring)=0.88 ppm.

[0095] Adhesive Example 1

[0096] This example provides a light-curing adhesive, and the specific preparation process is as follows:

[0097] Purchase polyurethane acrylic resin from the market, take 4.5g of polyurethane acrylic resin, 3.5g of silicon-containing monomer M1 prepared in Example 1 of silicon-containing monomer, 2g of acryloylmorpholine and 0.3g of photoinitiator 1173, mix them, and stir them evenly in a 65°C water bath to obtain a light-curing adhesive.

[0098] Adhesive Examples 2 to 5

[0099] Adhesive Examples 2 to 5 each provide a photocurable adhesive, which differs from Adhesive Example 1 in that the silicon-containing monomer M1 in Adhesive Example 1 is replaced with silicon-containing monomers M2 to M5 prepared in Silicon-containing Monomer Examples 2 to 5, respectively, to obtain the photocurable adhesives of Adhesive Examples 2 to 5.

[0100] Adhesive Comparative Example 1

[0101] This example provides a light-curing adhesive, and the specific preparation process is as follows:

[0102] Take 8g of polyurethane acrylic resin, 2g of acryloylmorpholine and 0.3g of photoinitiator 1173, mix them, and stir them evenly in a 65℃ water bath to obtain a light-curing adhesive.

[0103] Performance Testing

[0104] (1) The photocurable adhesives obtained from Adhesive Examples 1 to 5 and Adhesive Comparative Example 1 were tested for their bonding performance. The specific standard was GB / T 33333-2016. The testing process was as follows: Each test sample was poured into a customized mold, left to stand for 5 minutes, and then radiated and cured for 10 seconds using a mercury lamp with a radiation intensity of 250 mJ·cm -2 , a fully cured film can be obtained. The finished product is cut into a shape of 25mm×10mm, placed between iron sheets and squeezed for 2 minutes with a force of 5MPa to obtain a bonding sample. The Shenzhen Sansi Zongheng UTM4202 electronic universal testing machine is used to test the bonding performance of the sample. The bonding sample is separated with a force parallel to the bonding surface. The test process diagram is shown in the figure. Figure 1 As shown, the tensile shear strength of the sample is tested and recorded, which can be used to judge the strength of its bonding performance.

[0105] (2) In order to observe the change of the bonding performance of the samples with the extension of the placement time, a durability test was carried out. The specific standard refers to GB / T 33333-2016. The test process is as follows: prepare the bonding samples according to the steps in the performance test (1). After the prepared bonding samples are placed for seven days, the bonding performance of the samples is tested using an electronic universal testing machine to determine the change of the bonding performance.

[0106] (3) Conduct a hydrophobic performance test. The specific standard is GB / T 30693-2014. The test process is as follows: prepare the bonding sample according to the steps in the performance test (1), and use Shanghai Zhongchen JC2000C1 contact angle measuring instrument to test the water contact angle of the sample surface.

[0107] (4) Conduct thermal stability test. The specific standard refers to GB / T 27761-2011. The test process is as follows: prepare the bonding sample according to the steps in performance test (1). Use a German NETZSCH thermogravimetric analyzer to test the thermal stability of the sample in a nitrogen atmosphere at a heating rate of 10°C / min in the range of 35°C to 750°C. The nitrogen flow rate is 20 mL / min. Obtain the thermal decomposition temperature and residual carbon rate of the sample. The residual carbon rate is calculated based on the undecomposed mass and the original mass.

[0108] The test results are shown in Table 1.

[0109] Table 1 Performance test results of the photocurable adhesives obtained from adhesive examples 1 to 5 and adhesive comparative example 1

[0110]

[0111]

[0112] As can be seen from Table 1, the adhesive comparative example 1 does not add the silicon-containing monomer, and the obtained bonding performance, durability, thermal stability and hydrophobicity are all worse than those of the adhesive examples 1 to 5. The water contact angle pictures of the adhesive examples 1 to 5 and the adhesive comparative example 1 are as follows: Figure 2 As shown, (a) is adhesive example 1, (b) is adhesive example 2, (c) is adhesive example 3, (d) is adhesive example 4, (e) is adhesive example 5, and (f) is adhesive comparative example 1. Figure 2 It can be seen that, compared with the adhesive comparative example 1, the adhesive examples 1 to 5 of the present invention have better hydrophobic effect.

[0113] As can be seen from the above examples, in the preparation method of the silicon-containing monomer of the embodiment of the present invention, the acrylate double bond required for curing is first introduced by reacting the hydrogen bond with the isocyanate, and then the amino group is reacted with the isocyanate group to generate the substituted urea. The reaction is rapid and the steric hindrance caused by the previous step reaction can be ignored, making the preparation process of the monomer more convenient. In addition, the acrylate raw material used in the embodiment of the present invention contains a relatively long chain segment and an active double bond, which can not only give the adhesive flexibility, but also participate in curing.

[0114] The photocurable adhesive of the embodiment of the present invention has active groups such as siloxane bond, urea bond, urethane bond and acrylate double bond due to the introduction of silicon-containing monomers, which can obtain good flexibility and adhesion while reducing the impact of environmental water vapor on the product, enhancing practicality and durability, and can reduce the viscosity of the system, reduce the generation of internal bubbles, thereby increasing the transparency and durability of the adhesive, and obtaining good adhesion; the silicon-containing monomer combined with the matrix resin (such as polyurethane acrylate resin, etc.) can further enhance the hydrogen bond concentration of the system, thereby improving the adhesion of the adhesive. In addition, the photocurable adhesive in the embodiment of the present invention can be cured and cross-linked under ultraviolet light, which is more convenient to use than traditional liquid adhesives; and the adhesive has lower surface energy and good defoaming performance, so that less bubbles can be generated without adding a defoamer, and a product with good transparency and durability is obtained, which is also conducive to simplifying the raw material formula and reducing the preparation cost; in addition, the adhesive has good flexibility, heat resistance and durability, and can be widely used in bonding between various materials.

[0115] In summary, in the silicon-containing monomer of the present invention, the siloxane bond can give the system good flexibility, adhesion, water resistance, transparency and other properties, and in a humid environment, the siloxane bond can hydrolyze and crosslink with water, which can increase the crosslinking density and enhance adhesion; the urea bond and the urethane bond can increase the hydrogen bond concentration of the system, thereby improving the adhesion; the acrylate double bond is conducive to the rapid curing of the monomer and improves the preparation efficiency. Using the silicon-containing monomer of the present invention, a light-curing adhesive with few bubbles, strong adhesion, high transparency and good durability can be prepared to achieve firm bonding between a variety of materials.

Claims

1. A silicon-containing monomer, characterized in that: The structural formula of the silicon-containing monomer is shown in the following formula (I): In formula (I), R1 represents a C1-C30 alkyl group or a C6-C30 aromatic group; R2 represents a C1-C30 alkyl group, and is optionally interrupted by one or more O atoms, and / or interrupted by one or more -C(=O)O-; R3 represents a C1-C30 alkyl group; R4-R6 each independently represent a C1-C20 alkyl group.

2. The silicon-containing monomer according to claim 1, characterized in that R1 represents a C3-C20 branched or straight chain alkyl group, a C3-C20 cycloalkyl group substituted or unsubstituted by a C1-C5 alkyl group, or a C6-C20 aromatic group substituted or unsubstituted by a C1-C5 alkyl group; and / or, R2 represents a C3-C20 alkyl group, and is optionally interrupted by 1-10 O atoms, and / or interrupted by 1-10 -C(=O)O-; and / or, R3 represents a C1-C20 alkyl group; And / or, R4 to R6 each independently represent a C1 to C10 alkyl group.

3. The silicon-containing monomer according to claim 1, characterized in that R1 means And / or, R2 represents and / or, R3 represents a C3-C12 alkyl group; and / or, R4 to R6 each independently represent a methyl group or an ethyl group.

4. The silicon-containing monomer according to claim 1, characterized in that The silicon-containing monomer comprises:

5. A method for preparing a silicon-containing monomer according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing the diisocyanate containing R1 with a polymerization inhibitor, adding an acrylate containing R2 and a catalyst, and performing a first polymerization reaction to obtain an intermediate; S2, mixing the intermediate obtained in step S1 with a silane coupling agent containing R3 to R6, and performing a second polymerization reaction to obtain the silicon-containing monomer.

6. The preparation method according to claim 5, characterized in that: The diisocyanate containing R1 includes at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate or hexamethylene diisocyanate; and / or, the acrylate containing R2 includes at least one of 2-(acryloyloxy)ethyl-6-hydroxycaproate, dicaprolactone-2-(acryloyloxy)ethyl ester or 20-hydroxy-3,6,9,12,15,18-hexaoxaeicos-1-yl acrylate; And / or, the silane coupling agent containing R3 to R6 includes at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 4-aminobutyltriethoxysilane, aminomethyltriethoxysilane or 11-aminoundecyltriethoxysilane; and / or, the polymerization inhibitor comprises at least one of hydroquinone, imidazoline, catechol or hydroquinone; and / or, the catalyst comprises at least one of bis(dimethylaminoethyl)ether, pentamethyldiethylenetriamine, dimethylcyclohexylamine, dibutyltin dilaurate, organic bismuth or triazine trimerization catalyst; and / or, the molar ratio of the diisocyanate containing R1 to the acrylate containing R2 is 1:(1-1.1); and / or, the molar ratio of the intermediate to the silane coupling agent containing R3 to R6 is 1:(1 to 1.1); and / or, based on the total mass of the diisocyanate containing R1 and the acrylate containing R2, the amount of the polymerization inhibitor is 600 to 1000 ppm; And / or, based on the total mass of the diisocyanate containing R1 and the acrylate containing R2, the amount of the catalyst used is 1000-2000 ppm.

7. The preparation method according to claim 5, characterized in that: The reaction temperature of the first polymerization reaction is 40 to 55° C. And / or, the reaction time of the first polymerization reaction is 1 to 4 hours; and / or, the reaction temperature of the second polymerization reaction is 50 to 80° C.; And / or, the reaction time of the second polymerization reaction is 1 to 4 hours; And / or, step S1 and step S2 are performed under an atmosphere of protective gas.

8. A light-curing adhesive, characterized in that: The preparation method comprises the following raw materials: a base resin, a photoinitiator, and the silicon-containing monomer according to any one of claims 1 to 4.

9. The light-curing adhesive according to claim 8, characterized in that: The photocurable adhesive comprises the following raw materials in parts by weight: 30 to 60 parts of base resin, 3 to 8 parts of photoinitiator, and 20 to 50 parts of silicon-containing monomer; And / or, the base resin includes at least one of polyurethane acrylic resin, epoxy resin or epoxy acrylate; and / or, the photoinitiator includes at least one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide or benzophenone.

10. The light-curing adhesive according to claim 8, characterized in that: The raw materials for preparing the photocurable adhesive further include acrylate monomers, defoamers or a combination thereof; the acrylate monomers include at least one of acryloylmorpholine, methyl acrylate, ethyl acrylate, 2-methyl methacrylate or 2-ethyl methacrylate.

Citation Information

Patent Citations

  • Preparation method of organosilane polyurethane acrylate and application of organosilane polyurethane acrylate in water-boiling-resisting ultraviolet light cured glass paint

    CN104628983A

  • Siloxane-containing polyacrylate capable of being moisture-cured at room temperature, and preparation method thereof

    CN111116821A

  • Ureido structure-containing UV (ultraviolet) moisture dual-curing organic silicon

    CN114292402A

  • Tackifying accelerant and preparation method and application thereof, and water-resistant bonding single-component polyurethane sealant and preparation method and application thereof

    CN115785850A

  • EB-cured scratch-resistant stain-resistant decorative film and preparation method thereof

    CN118791962A